A Suite of Intelligent Tools for Early Detection and Prevention of Blackouts in Power Interconnections - Voropai, N. I.; Tomin, N. V.; Sidorov, D. N.; Kurbatsky, V. G.; Panasetsky, D. A.; Zhukov, A. V.; Efimov, D. N.; Osak, A. B. (Automation and remote control, 2018)
We propose a suite of intelligent tools based on the integration of methods of agent modeling and machine learning for the improvement of protection systems and emergency automatics. We propose an online approach to the assessment and management of dynamic security of electric power systems (EPS) with the use of a streaming modification of the random forest algorithm. The suite allows to recognize dangerous modes of complex closed-loop EPS, preventing the risk of emergencies on early stages. We show results of experimental tests on IEEE test systems.